2011
DOI: 10.4103/0971-6203.79687
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric comparison of high dose rate brachytherapy and intensity-modulated radiation therapy for cervical carcinoma

Abstract: Intracavitary brachytherapy is an integral part of radiotherapy for locally advanced gynecologic malignancies. A dosimetric intercomparison of high dose rate intracavitary brachytherapy (HDR_BT) and intensity-modulated radiotherapy in cervical carcinoma has been made in the present study. CT scan images of 10 patients treated with HDR_BT were used for this study. A sliding-window IMRT (IMRT_SW) and step-and-shoot IMRT plans were generated using 6-MV X-rays. The cumulative dose volume histograms of target, blad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…For the both patient groups, sMLC_IL5 showed higher heterogeneity in PTV dose distribution than the others. These results are supported by the study performed by Shwetha et al (14) in which the performances of dynamic and static MLC‐based IMRT and high‐dose‐rate brachytherapy were compared for cervical carcinoma. They found that the IMRT plans based on sMLC_IL5 had the lowest HI performance with the average HI of 1.29±0.13 while the other IMRT plans based on dMLC, sMLC_IL10 and sMLC_IL20 had the average HI in the band of 1.19‐1.21.…”
Section: Discussionsupporting
confidence: 71%
“…For the both patient groups, sMLC_IL5 showed higher heterogeneity in PTV dose distribution than the others. These results are supported by the study performed by Shwetha et al (14) in which the performances of dynamic and static MLC‐based IMRT and high‐dose‐rate brachytherapy were compared for cervical carcinoma. They found that the IMRT plans based on sMLC_IL5 had the lowest HI performance with the average HI of 1.29±0.13 while the other IMRT plans based on dMLC, sMLC_IL10 and sMLC_IL20 had the average HI in the band of 1.19‐1.21.…”
Section: Discussionsupporting
confidence: 71%
“…Significant deviations may be most common in treatment techniques with steep dose gradients such as stereotactic body radiation therapy (SBRT), where dose decreases nearly isotropically in and around the target, 14 or high dose rate (HDR) brachytherapy, where absorbed dose in some voxels near the source can exceed the prescription dose by 200%. 15,16 Overall, such as when taking the mean dose across a structure, some of these errors may cancel out and this may account for the acceptance of the existing models to date, particularly in parallel organs, where the volume effect plays a greater role. 17 However, in serial organs such as the spinal cord, the accuracy of dosimetry at the voxel level is critical.…”
Section: Discussionmentioning
confidence: 99%
“…Important to note, when comparing OARs doses, the value of D 2cm 3 was always lower for ICBRT respect to IMRT. Several investigators [45,46] compared dosimetric parameters of the entire external OARs volumes with those of only the OARs wall volumes both for urinary bladder and rectum. When the volume of 2 cm 3 is considered, the D 2cm 3 values computed for the external contours are almost identical to the D 2cm 3 values for the organ wall.…”
Section: Discussionmentioning
confidence: 99%